2008
DOI: 10.1007/s00418-008-0524-6
|View full text |Cite
|
Sign up to set email alerts
|

Co-culture of canine mesenchymal stem cells with primary bone-derived osteoblasts promotes osteogenic differentiation

Abstract: Tissue engineering of bone grafts with osteogenic progenitor cells such as adult mesenchymal stem cells (MSC) represents a promising strategy for the treatment of large bone defects. The aim of this experimental study was to evaluate the osteogenic potential of primary osteoblasts on MSCs in co-culture at different ratios. The co-cultures were treated with or without a specific osteogenic induction medium in monolayer and high density cultures. In monolayer co-cultures, MSCs and osteoblasts actively searched f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
67
1
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(82 citation statements)
references
References 60 publications
7
67
1
7
Order By: Relevance
“…Csaki et al demonstrated that MSCs and osteoblasts actively search for cell-cell contact, leading to cell proliferation and osteogenic differentiation, only in monolayer co-cultures with osteoinductive treatment [14]. The quality of osteogenesis, as evidenced by protein expression, is proportional to the quantity of osteoblasts in the co-cultures, a finding that is consistent with our results.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Csaki et al demonstrated that MSCs and osteoblasts actively search for cell-cell contact, leading to cell proliferation and osteogenic differentiation, only in monolayer co-cultures with osteoinductive treatment [14]. The quality of osteogenesis, as evidenced by protein expression, is proportional to the quantity of osteoblasts in the co-cultures, a finding that is consistent with our results.…”
Section: Discussionsupporting
confidence: 92%
“…However, it remains unclear as to whether and how osteoblasts affect the self-renewal and differentiation of another major stem cell population in bone marrow MSCs. There is little in vivo data available on this, and in vitro studies using conditioned medium or co-culture models have produced inconsistent results [13][14][15][16][17]. In experiments using conditioned medium, the real-time dynamic cell-cell interactions are missing and osteogenic inducers such as dexamethasone were used.…”
Section: Introductionmentioning
confidence: 99%
“…These results are similar to the view that osteoblasts can promote MSC or hematopoietic progenitor cell proliferation [22][23] . Osteoblasts can also regulate osteogenic differentiation of MSCs in stimulating osteogenesis 24 .…”
Section: Discussionsupporting
confidence: 89%
“…Co-culture system allowed the contact of different cell types in vitro which ideally simulated the coexisting microenvironment of cells in vivo, thereby made it possible to investigate the molecular events during the crosstalk and made cell fate determination more controllable than directly injecting MSCs into tissues. The differentiation of MSCs affected by full differentiated cells in direct or indirect co-culture systems were investigated by a number of groups and differentiation of MSCs were achieved or promoted (Lange et al 1999;Lee et al 2007;Csaki et al 2009;Chen et al 2009;Wang et al 2006;Ball et al 2004). However, little is known about the proliferation and commitment of MSCs subjected to co-culture conditions with primary tenocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this in vitro culture system made MSCs fate more controllable than in vivo and easier for understanding the molecular events within the crosstalk of MSCs and the local environment. Co-culturing with appropriate cell types, MSCs have been elucidated to commit to corresponding lineages, such as osteoblasts (Csaki et al 2009), chondrocytes (Chen et al 2009), ligament cells (Lee et al 2007), cardiomyocytes , hepatocytes (Lange et al 1999) and smooth muscle cells Ball et al 2004). Interestingly, direct cell-to-cell contact has been proven to be indispensable for the commitment of a sort of cell types, such as smooth muscle cells and cardiomyocytes Ball et al 2004).…”
Section: Introductionmentioning
confidence: 99%